Kritik terhadap Rasionalitas: Integrasi Psikologis, Filosofis, dan Sosial-Kultural - Marselina Tangke Tondok; Sewin Datu Manik; Krisdayanti Krisdayanti; Ernianti Pakiding; Rimelda Anggona (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2025)
This study examines a critical perspective on the concept of rationality, which has long been regarded as the primary foundation of logical and objective decision-making. Using a qualitative approach through a literature study method, this research explores the integration of psychological, philosophical, and socio-cultural dimensions in understanding the limitations and complexities of human rationality. The findings reveal that rationality is not entirely neutral or free from bias. The psychological perspective highlights the influence of cognitive biases such as confirmation bias and anchoring effect, which often turn rationality into a justification for emotionally driven decisions. From a philosophical standpoint, David Hume’s argument that “reason is the slave of the passions” emphasizes the subordination of reason to emotion, while Horkheimer and Adorno reveal how modern rationality has evolved into an instrument of domination through ideologies of efficiency and control. In the socio-cultural dimension, rationality is shown to be non-universal, shaped by specific cultural and historical contexts, as exemplified by Max Weber’s concept of the “iron cage,” describing how individuals become trapped within bureaucratic systems of rationalization. The study concludes that classical rationality, characterized by its deterministic and calculative nature, is inherently bounded and insufficient to address the uncertainty and complexity of the modern world. Therefore, a new paradigm of rationality is needed—one that is integrative, reflective, and humanistic, combining logic with emotional, ethical, and social dimensions to produce decisions that are not only rational but also just and humane.